2019
DOI: 10.1016/j.btre.2019.e00316
|View full text |Cite|
|
Sign up to set email alerts
|

Commercial application of cellulose nano-composites – A review

Abstract: Highlights Extraction methods of nanocellulose. Surface modification of cellulose fibers. Cellulose nanofiber-reinforced nanocomposite processing and applications. Scaling up Nanocellulose Production technology. Latest patents trends on cellulose nanocomposites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
317
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(324 citation statements)
references
References 102 publications
1
317
0
6
Order By: Relevance
“…In addition, they are very good raw material for several industrial processes due to their lignocellulosic composition. For example, carbon fibers from lignin, cellulose whiskers, bioethanol from cellulose, and hemicellulose can be obtained [50]. Likewise, their high volatile matter and low ashes content make them ideal for gasification processes; however, only U. europaeus is ideal for activated carbon obtention due to its fixed carbon content [34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they are very good raw material for several industrial processes due to their lignocellulosic composition. For example, carbon fibers from lignin, cellulose whiskers, bioethanol from cellulose, and hemicellulose can be obtained [50]. Likewise, their high volatile matter and low ashes content make them ideal for gasification processes; however, only U. europaeus is ideal for activated carbon obtention due to its fixed carbon content [34].…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrate scaffolds such as chitosan, cellulose, agar‐agar and alginates, and derivatives thereof, are industrially employed immobilization matrices for enzymes and peptides anchored at high surface densities (Amalraj, Gopi, Thomas, & Haponiuk, ; Bilal & Iqbal, ; Seabra, Bernardes, Fávaro, Paula, & Durán, ; Zdarta, Meyer, Jesionowski, & Pinelo, ). Among those, especially cellulose nanocrystal formulations are being tested for multifunctional layouts, for instance in biomedical and nutraceutical products (Amalraj et al, ; Seabra et al, ; Sharma, Thakur, Bhattacharya, Mandal, & Goswami, ). For installing spatially and stoichiometrically well‐defined biomolecule ensembles (“modules” in Figure ) on predictably shaped nanocarriers, however, protein and nucleic acid biopolymers offer important additional degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, various applications of plants used as bioresources are discussed, providing valuable raw materials used as additives in polymeric matrices, such as lignocellulosic fibers [69] and nano-cellulose [70], as well as plant extracts containing bioactive phenolic compounds [42] used in the pharmaceutical and cosmetic industries [71]. The increasing environmental concerns draw attention on their use as active compounds, instead of synthetic ones.…”
Section: Lignocellulosic Materials and Plant Extracts In Polymeric Comentioning
confidence: 99%
“…Nanocellulose fibrils, which are the building blocks of plant cell [95] walls and give plants and trees their structural strength and stiffness, are a very interesting and well-studied nanoscale natural material that can potentially improve the properties of the polymers [96]. Many studies have already reported on use of nanocellulose in different forms for composite applications [70]. Cellulose nanomaterials are considered as a suitable solution to replace commonly used inorganic nanofillers [97] because they are widely available, renewable, and biodegradable [96].…”
Section: Nanocellulosementioning
confidence: 99%